(untitled) (Islas, 2024)
Introduction: This article presents a proposal for systematizing the behavior of literary journalism in Cuba between 1959 and 1990. Methods: The study was conducted from a qualitative approach, supported by the methods of analysis-synthesis, inductive, historical-logical analysis; technical-narrative and journalistic analysis, as well as interviews with various actors. Results: A systemic view is provided that seeks to articulate this journalistic modality, printed media, and their connections within the cultural field amid radical transformations in the public communication system of the Island between 1959 and 1990. Conclusions: During the studied period, literary journalism went through four stages with actors, publications, styles in the construction of informative discourse, and dynamics that make them distinct from one another.